Medical ethnobotany and utilization of medicinal plants in the Don Pu Ta Forest Thai Yoi Ethnic Groups, Sakon Nakhon Province in the Northeastern Thailand (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Saensouk S, Saensouk P, Ragsasilp A, Senakun C, Daovisan H, Setyawan AD, Niamngon T, Niamngon P, Appamaraka S. 2024. Medical ethnobotany and utilization of medicinal plants in the Don Pu Ta Forest Thai Yoi Ethnic Groups, Sakon Nakhon Province in the Northeastern Thailand. Biodiversitas 25: 3014-3031. The Thai Yoi Ethnic Group has access to Don Pu Ta Forest, a valuable resource rich in medicinal plants that are essential to the community. Local doctors in Don Pu Ta Forest have traditionally used these medicinal plants to care for the health of the community. This study aimed to examine the plant species and the use of medicinal plants in Don Pu Ta Forest, located in Pak Thop Village, Pla Lo Sub-district, Waritchaphum District, Sakon Nakhon Province, Thailand. The study was conducted from 2023 to 2024 by interviewing villagers and surveying the biodiversity of medicinal plants. The plots were created to collect data on plant species, which were then examined and analyzed using various indices. The results of the study identified 36 families, 54 genera, and 61 species of medicinal plants. These species were further categorized into 30 families and 50 species of tall trees, 20 families and 25 species of saplings, and 14 families and 18 species of understory plants. Among these, tall trees had the highest diversity score, measuring 3.88, followed by saplings with a diversity value of 2.87, and understory plants with a diversity index of 2.46. The Evenness Index (E) was 0.88, and the highest Importance Value Index (IVI) recorded was 27.66. Specifically, Lagerstroemia calyculata Kurz had the highest IVI at 27.66, followed by Elaeocarpus lanceifolius Roxb. at 22.30, and Anisoptera costata Korth. at 20.20. The ICF analysis revealed that a total of 61 herbs were used to treat 28 groups of symptoms. The herbal treatment for relieving symptoms of flatulence, bloating, and cramps had the highest ICF value at 0.96, while the lowest ICF value was 0.70. Seven plants used to treat similar symptoms showed the highest fidelity level (%FL) value of 100%. This research is vital for the effective use of herbal plants in Don Pu Ta Forest and for conserving plant genetics to ensure long-term sustainability.
Keywords: Don Pu Ta Forest, ethnobotany, medicinal plants, Thai Yoi Ethnic Group